People solve rebuses unwittingly—Both forward and backward: Empirical evidence for the mental effectiveness of the signifier - Olyff, Giulia; Bazan, Ariane (Frontiers in Human Neuroscience, 2023)
Freud (1909) proposed that names of clinically salient objects or situations, such as for example a beetle (Käfer) in Mr. E’s panic attack, refer through their phonological word form, and not through their meaning, to etiologically important events – here, ‘Que faire?’ which summarizes the indecisiveness of Mr. E’s mother concerning her marriage with Mr. E’s father. Lacan formalized these ideas, attributing a full-fledged mental effectiveness to the signifier and summarized this as “the unconscious structured as a language”. We tested one aspect of this theory, namely that there is an influence of the ambiguous phonological translation of the world upon our mental processing without us being aware of this influence. For this, we used a rebus priming paradigm, including 14 French rebuses, composed of two images depicting common objects, such as, paon /pɑ̃/ ‘peacock’ and terre /tεr/ ‘earth’, together forming the rebus panthère /pɑ̃tεr/ ‘panther’. These images were followed by a target word semantically related to the rebus resolution, e.g., félin or ‘feline’, upon which the participants, unaware of the rebus principle, produced 6 written associations. 1458 participants were randomly assigned either to Experiment 1 in which they were shown the rebus images in either forward or in reverse order or to Experiment 2, in which they were shown only one of both rebus images, either the first or the last. The results show that the images induced inadvertent rebus priming in naïve participants. In other words, our results show that people solve rebuses unwittingly independent of stimulus order, thereby constituting empirical evidence for the mental effectiveness of the signifier.